A History of Hell: The Jewish Origins of the Idea of Gehenna in the Synoptic Gospels. - Lusthaus, Jonathan (Australian religion studies review, 2008)
Hell is a fundamentally important Christian doctrine, but questions still remain about precisely how the concept developed. This article goes a small way to addressing such questions by attempting to ascertain the immediate origins of the idea of Gehenna, a key element of the doctrine of hell found in the Synoptic Gospels. In the Synoptics, Gehenna is the otherworldly location of eternal punishment for the wicked, after the last judgement. This article argues that while Zoroastrian, Mesopotamian, Egyptian and Greek ideas may have influenced Jewish and early Christian eschatology, the idea of Gehenna appears to have developed directly out of Jewish canonical and extra-canonical sources. The word Gehenna is actually the Greek form of Ge-Hinnom, the name of a valley outside Jerusalem mentioned in the Hebrew Bible. Furthermore, the four central elements that allowed the transformation from valley to eschatological site of eternal punishment are all found in Jewish writings.